Phenotypic stability of spring bread wheat regenerant lines - V. Yu. Stupko; A. V. Sidorov (Труды по прикладной ботанике, генетике и селекции)
Background. Selection of somaclonal variation under callus culture (СС) conditions is one of the methods of undirected genome change induction which has become actively used in the development of cultivars with high adaptive potential. The aim of the present study was the estimation of the applicability of dedifferentiated cell culture to obtain cultivars with different levels of phenotypic stability.Materials and methods. Ten wheat regenerant lines (RLs), obtained under selective (NaCl, low pH, drought) and nonselective conditions on the basis of СС were assessed along with their donor genotypes or the ones considered equivalent to them (in the case where the breeding variety was a donor) under field conditions on plots of 1 m2. 1000 grain weight data were used for the evaluation of the agronomic (bi, s2di) and biological (σ2САСi) stability. The yield-based superiority measure (Pi) was also calculated.Results. RLs from cv. ‘Novosibirskaya 15’ were more stable than their donor genotype from the biological viewpoint as well as from the agronomic one. The GGE-biplot analysis shows that they belong to the same “environment” (sector) with the vertex genotype ‘Novosibirskaya 15’ with bi being close to 1. Cv. ‘Tayozhnaya’ and its high-yielding salt tolerant RL RS(Tayozhnaya)3.6 were located in the opposite sectors and appeared to be highly stable genotypes. They are considered to be better adapted to low-yielding locations (bi < 0,7) along with the RZ(К-79-2)7.16 RL, selected for drought tolerance. The RLs from the high-yielding K-142-4 line showed a wide range of values of the stability parameters. They were better adapted to high-yielding locations than their reference genotype, cv. ‘Minusa’. Thus, its RL had a low stability of 1000 grain weight.Conclusion. Consequently, cell selection is a valuable source of breeding material that differs significantly in phenotypic stability both from the donor genotype and from other RLs, developed under CC of the same donor plant.